Composition, microstructure and electrical properties of K0.5Na0.5NbO3 ceramics fabricated by cold sintering assisted sintering. Issue 4 (April 2019) - Ma, Jianzhang; Li, Hanying; Wang, Huajing; Lin, Cong; Wu, Xiao; Lin, Tengfei; Zheng, Xinghua; Yu, Xing
Abstract: In this paper, cold sintering was served as a forming method to assist the conventional sintering, which is so-called cold sintering assisted sintering (CSAS) method. Lead-free K0.5 Na0.5 NbO3 piezoelectric ceramics were prepared by the CSAS method, and the effects of the different procedures on the sintering behaviors and electrical properties of KNN ceramics were studied. Compared with conventional sintering (CS), cold sintering process can induce potassium-rich phase on the KNN particle surface, and remarkably increase both the green and sintering density of KNN ceramics. Meanwhile, the potassium-rich phase would transform to K4 Nb6 O17 second phase on the grain surface, and subsequently suppress the volatilization of potassium element. The sinterability and electrical properties were greatly improved, and KNN piezoelectric ceramics with high performance can be manufactured in a wide sintering temperature range (1055 °C–1145 °C), which proves that CSAS has the potential to be an excellent sintering technique for producing KNN based ceramics.